2005
DOI: 10.1128/jcm.43.4.1768-1775.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR Testing of Ethanol-Fixed Nasal Swab Specimens as an Augmented Surveillance Strategy for Influenza Virus and Adenovirus Identification

Abstract: Viral culture isolation has been widely accepted as the "gold standard" for laboratory confirmation of viral infection; however, it requires ultralow temperature specimen storage. Storage of specimens in ethanol at room temperature could expand our ability to conduct active surveillance and retrospective screenings of viruses with rapid and inexpensive real-time PCR tests, including isolates from remote regions where freezing specimens for culture is not feasible. Molecular methods allow for rapid identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 50 publications
0
55
0
2
Order By: Relevance
“…This was measured by real-time PCR with a conserved 93-bp region of the matrix gene, as described (3). Although the data were not quantitative, we found that samples preserved with either commercial or guanidine buffers had approximately 10-to 100-fold less amplifiable viral RNA than observed for cloacal swabs on the basis of C T values (data not shown), whereas alcohols had approximately 1000-to 10,000-fold less (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was measured by real-time PCR with a conserved 93-bp region of the matrix gene, as described (3). Although the data were not quantitative, we found that samples preserved with either commercial or guanidine buffers had approximately 10-to 100-fold less amplifiable viral RNA than observed for cloacal swabs on the basis of C T values (data not shown), whereas alcohols had approximately 1000-to 10,000-fold less (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Our experience with fixed specimens in virus surveillance previously employed ethanol as a preservative (3,9). Although ethanol has been useful in the identification of influenza Apositive samples, it was insufficient to efficiently identify subtypes by RT-PCR (data not shown).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Newer methods that avoid this growth step, however, will facilitate direct high-throughput analysis of native samples from surveillance. This will include active samples preserved by cold chain as well as inactive samples preserved by chemical inactivation (Krafft 2005, Ilyushina 2005, Runstadler 2007). Since very little sequence information exists for may influenza subtypes, PCR primers will be updated and improved in an iterative fashion (see paper by Song et al in Appendices).…”
Section: Genotypingmentioning
confidence: 99%